Inovasi Guru dalam Metode Pembelajaran Berhitung untuk Menstimulasi Kecerdasan Logis-Matematis di TK Kalyca Montessori School Yogyakarta - Novita, Anggria; Muqowim, Muqowim (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2019)
The focus of this research is to find out the learning background. This research is a qualitative descriptive method with a case study. Data collection techniques are interviews, observation, and documentation. The results of this study are an important reason for teachers to innovate in learning to count is to be facilitators and observers, teachers as learners, adopters, developers, and creators; the teacher's innovation process in the three stages of learning through introductory concepts, transitions/ stages, and symbol stages; and effects of teacher innovation in numeracy learning methods to stimulate logical-mathematical intelligence to be able to think logically, be able to improve memory, be able to classify, be able to increase numbers, be able to find ways to work, become problem solvers, able to understand cause and effect, and be able to improve accuracy.